SHRIMP U-Pb dating of high-grade migmatites and related magmatites from northwestern Oates Land (East Antarctica): evidence for a single high-grade event of Ross-Orogenic age - Henjes-Kunst, F.; Roland, N.; Dunphy, J.; Fletcher, Ian (Terra Antartica Publication, Museo Nazionale dell'Antartide 'Felice Ippolito', 2004)
High- to very-high-grade migmatitic basement rocks of the Wilson Hills area in northwestern Oates Land (Antarctica) form part of a low-pressure high-temperature belt located at the western inboard side of the Ross-orogenic Wilson Terrane. Zircon, and in part monazite, from four very-high grade migmatites (migmatitic gneisses to diatexites) and zircon from two undeformed granitic dykes from a central granulite-facies zone of the basement complex were dated by the SHRIMP U-Pb method in order to constrain the timing of metamorphic and related igneous processes and to identify possible age inheritance. Monazite from two migmatites yielded within error identical ages of 499 ± 10 Ma and 493 ± 9 Ma. Coexisting zircon gave ages of 500 ± 4 Ma and 484 ± 5 Ma for a metatexite (two age populations) and 475 ± 4 Ma for a diatexite. Zircon populations from a migmatitic gneiss and a posttectonic granitic dyke yielded well-defined ages of 488 ± 6 Ma and 482 ± 4 Ma, respectively. There is only minor evidence of age inheritance in zircons of these four samples. Zircon from two other samples (metatexite, posttectonic granitic dyke) gave scattered 206Pb-238U ages.While there is a component similar in age and in low Th/U ratio to those of the other samples, inherited components with ages up to c. 3 Ga predominate. In the metatexite, a major detrital contribution from 545 - 680 Ma old source rocks can be identified. The new age data support the model that granulite- to high-amphibolite-facies metamorphism and related igneous processes in basement rocks of northwestern Oates Land were confined to a relatively short period of time of Late Cambrian to early Ordovican age. An age of approximately 500 Ma is estimated for the Ross-orogenic granulite-facies metamorphism from consistent ages of monazite from two migmatites and of the older zircon age population in one metatexite. The variably younger zircon ages are interpreted to reflect mineral formation in the course of the post-granulite-facies metamorphic evolution, which led to a widespread high-amphibolite-facies retrogression and in part late-stage formation of ms+bi assemblages in the basement rocks and which lasted until about 465 Ma. The presence of inherited zircon components of latest Neoproterozoic to Cambrian age indicates that the high- to very-grade migmatitic basement in northwestern Oates Land originated from clastic series of Cambrian age and, therefore, may well represent the deeper-crustal equivalent of lower-grade metasedimentary series of the Wilson Terrane.